Investigation of the weathering effect on the 40Ar-39Ar ages of Antarctic meteorites - Kaneoka, Ichiro (1983)
P(論文) In order to examine the weathering effect on ^<40>(Ar)-^<39>(Ar) ages of Antarctic meteorites, the ^<40>(Ar)-^<39>(Ar) age patterns were compared for the outer and inner portions of two Antarctic meteorites (ALH-761,ALH-77288). The results indicate that the oxidized outer portions show anomalously old ^<40>(Ar)-^<39>(Ar) ages which exceed 4600Ma in the intermediate temperature fractions of around 800-1000℃. These old ^<40>(Ar)-^<39>(Ar) ages are accompanied by the increase of ^<36>(Ar), which is regarded to be mostly of atmospheric ^<36>(Ar). This might be explained by the incorporation of atmospheric Ar in hematite which was produced from goethite during neutron irradiation. The inner relatively fresh portions show the following plateau ages : ALH-761,64,4487±50Ma; ALH-77288,63,4497±40Ma. departmental bulletin paper